2009
DOI: 10.1007/s10664-009-9106-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the understandability of UML statechart diagrams with composite states—A family of empirical studies

Abstract: The main goal of this work is to present a family of empirical studies that we have carried out to investigate whether the use of composite states may improve the understandability of UML statechart diagrams derived from class diagrams. Our hypotheses derive from conventional wisdom, which says that hierarchical modeling mechanisms are helpful in mastering the complexity of a software system. In our research, we have carried out three empirical studies, consisting of five experiments in total. The studies diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 48 publications
(72 reference statements)
0
40
0
2
Order By: Relevance
“…In a closely relevant domain of software modeling, Cruz-Lemus et al [17] presents a family of experiments investigating the effect of hierarchy on the understandability of UML statechart diagrams (which are used not only to model software but also business processes). The results indicate insignificant or varied effects of hierarchy on understandability.…”
Section: Related Workmentioning
confidence: 99%
“…In a closely relevant domain of software modeling, Cruz-Lemus et al [17] presents a family of experiments investigating the effect of hierarchy on the understandability of UML statechart diagrams (which are used not only to model software but also business processes). The results indicate insignificant or varied effects of hierarchy on understandability.…”
Section: Related Workmentioning
confidence: 99%
“…As suggested by a previous study [26], we employed the mean value obtained using dynamic models minus the mean value achieved when not using them to calculate the effect sizes for Comprehension for each of the individual experiments, and from these values, we obtained the Hedges' g metric [38], [43], which was used as a standardized measure. This value expresses the magnitude of the effect of Method which, in our case is the use of dynamic models that are relative to the withingroup standard deviations.…”
Section: Meta--analysismentioning
confidence: 99%
“…For example, Cruz-Lemus et al [26] presented a controlled experiment on UML statechart comprehension. This study revealed that the use of composite states in a UML statechart improves the understandability of the diagrams when subjects had previous used them.…”
Section: Uml Behavioral Diagramsmentioning
confidence: 99%
“…Methods and guidelines for empirical research in general [23] and more specifically in software engineering [24] , are being also adapted and applied in the modeling and consistency related research [25], [26], [27], [28] as a means to obtain data and perform empirical evaluation.…”
Section: Research Background and Related Workmentioning
confidence: 99%